(untitled) (Atti del Sodalizio Glottologico Milanese, 2019)
The paper discusses some problems that searcher must face when he investigates the etymology of a word. After a short discussion of general problems, I present some etymologies of Armenian words: erivar ‘horse’ (from *roi-bho, originally ‘[animal] brown’, cf. Lithuanian raibas ‘shy’) and consider methodological questions about the etymologies of amusin ‘wife’ (from am- ‘together’ and the root *euk- ‘to accostumate’) and tʽoṙn ‘grandson’, connected with OInd. tarṇas ‘young animal’ and Lith. tar͂nas ‘servant’. KEYWORDS: Armenian, etymology, horse, wife, grandson